The Manipulus florum, Johannes Nider’s Formicarius, and Late Medieval Misogyny in the Construction of Witches prior to the Malleus maleficarum - Nighman, Chris (The Journal of Medieval Latin, 2014)
Abstract This article demonstrates and analyses Johannes Nider’s reception of Thomas of Ireland’s Manipulus florum, a popular early fourteenth-century florilegium, in composing the fifth book of his Formicarius, a very influential text for the development of the gendered witch stereotype in the fifteenth century. It also examines the lemmata “Mulier” and “Coniugium” in the Manipulus, arguing that Thomas of Ireland’s construction of those topics was essentially misogamous, rather than misogynous, though its reception by Nider was informed by misogyny. Abstract Cet article montre et analyse la réception par Johannes Nider du Manipulus florum, un florilège populaire compilé au début du quatorzième siècle, en composant le cinquième livre de son Formicarius, un texte très influent pour le développement du stéréotype de la sorcière dans le quinzième siècle. Il examine également les lemmes « Mulier » et «Coniugium » dans le Manipulus, faisant valoir que la construction de Thomas de l’Irlande de ces sujets était essentiellement contre la matrimonie, plutôt que misogyne, même si sa réception par Nider a été informée par la misogynie.